Rethinking Corporate Governance and Tax Avoidance, Evidence from Indonesia’s Basic Materials Firms - Mahroji Mahroji; Yenni Ayu Safitri (Universitas Mercu Buana, 2026)
Objectives: This study examines the effects of profitability, financial distress, firm size, CEO narcissism, board size, and female directors on tax avoidance among basic materials firms listed on the Indonesia Stock Exchange during 2021-2024. Methodology: This study uses secondary data from annual reports and financial statements of 13 firms, resulting in a balanced panel of 52 observations, and estimates pooled OLS with robust standard errors. Findings: Firm size has a negative association with tax avoidance, while board size and female directors have positive associations; profitability, financial distress, and CEO narcissism are not statistically strong. Conclusion: Governance characteristics do not always reduce tax avoidance linearly in basic materials firms with heterogeneous asset structures and tax planning incentives.